Pengaruh pemberian dosis pupuk organik cair terhadap pertumbuhan tanaman tomat - Fadlilah, Mutimatul (Maliki Interdisciplinary Journal, 2025)
Tomato plants (Lycopersicum esculentum) are important horticultural commodities in Indonesia that have high economic value and are widely consumed directly or as industrial raw materials. The growth of tomato plants is strongly influenced by environmental factors such as light intensity, water, and fertilizer dosage. The data used in this study is the result of naming tomatoes for approximately 40 days. This study aims to determine the effect of fertilizer doses on tomato growth. The dose of tomato plant fertilizer is divided into 4 treatments, namely 3 ml/L, 6ml/L, 9 ml/L and 12ml/L. This study was calculated manually and using minitab software to get the result that there is no effect of fertilizer dosing on tomato growth.